High-Alpine Permafrost and Active-Layer Soil Microbiomes Differ in Their Response to Elevated Temperatures - Luláková, Petra; Perez-Mon, Carla; Šantrůčková, Hana; Ruethi, Joel; Frey, Beat (Frontiers in Microbiology, 2019)
The response of microbial communities to the predicted rising temperatures in alpine regions might be an important part of the ability of these ecosystems to deal with climate change. Soil microbial communities might be significantly affected by elevated temperatures, which influence the functioning of soils within high-alpine ecosystems. To evaluate the potential of the permafrost microbiome to adapt to short-term moderate and extreme warming, we set up an incubation experiment with permafrost and active soil layers from northern and southern slopes of a high-alpine mountain ridge on Muot-da-Barba-Peider in the Swiss Alps. Soils were acclimated to increasing temperatures (4 to 40°C) for 26 days before being exposed to a heat shock treatment of 40°C for 4 days. Alpha-diversity in all soils increased slightly under gradual warming, from 4°C to 25°C, but then dropped considerably at 40°C. Similarly, heat shock induced strong changes in microbial community structures and functioning in the active layer of soils from both north-western and south-eastern slope aspects. In contrast, permafrost soils showed only minor changes in their microbial community structures and no changes in their functioning, except regarding specific respiration activity. Shifts in microbial community structures with increasing temperature were significantly more pronounced for bacteria than for fungi, regardless of the soil origin, suggesting higher resistance of high-alpine fungi to short-term warming. Firmicutes, mainly represented by Tumebacillus and Alicyclobacillaceae OTUs, increased strongly at 40°C in active layer soils, reaching almost 50% of the total abundance. In contrast, Saccharibacteria decreased significantly with increasing temperature across all soil samples. Overall, our study highlights the divergent responses of fungal and bacterial communities to increased temperature. Fungi were highly resistant to increased temperatures compared to bacteria, and permafrost communities showed surprisingly low response to rising temperature. The unique responses were related to both site aspect and soil origin indicating that distinct differences within high-alpine soils may be driven by substrate limitation and legacy effects of soil temperatures at the field site.